The Effect of The Self-Healing Method With The Butterfly Hug Technique On Changes In Maternal Anxiety Levels In The Latent Phase of Labor In Rumah Sakit Bersalin Paradise Tanah Bumbu - Tika Sari Dewy; Ritna Udiyani; Nadia Khairunnisa (International Journal of Health and Pharmaceutical (IJHP), 2026)
Anxiety in latent labor is a psychological response that can hinder labor by increasing stress hormones and tension in the muscles of the birth canal. Therefore, non-pharmacological treatments such as self-healing with the butterfly hug technique are necessary. This study aimed to determine the effect of self-healing with the butterfly hug technique on anxiety levels in latent labor. The study design used a Quasi-Experimental design with a one-group pretest-posttest. A sample of 10 mothers in the latent phase of labor who met the inclusion criteria (primigravida, maternal age <20->35 years) was obtained using an accidental sampling technique. The measurement instrument used the Pregnancy Related Anxiety Questionnaire-Revised 2 (PRAQ-R2) questionnaire. The intervention was carried out for 10 minutes with a butterfly hug procedure according to standard operating procedures. The results of the study showed that before the intervention, most (60%) mothers experienced moderate anxiety and after the intervention, most (60%) experienced mild anxiety. The results of the bivariate analysis using the Wilcoxon Test obtained a P-Value = 0.002 (<0.05) which means H0 is rejected and H1 is accepted. In conclusion, there is a significant influence of the self-healing method with the butterfly hug on the level of anxiety of mothers in the latent phase of labor. It is hoped that respondents can practice the butterfly hug technique independently as an effort to control anxiety during pregnancy.